Effects of Community-Based Cardiac Rehabilitation on Body Composition and Physical Function in Individuals with Stable Coronary Artery Disease: 1.6-Year Followup. (25th June 2013) - Mandic, Sandra; Hodge, Claire; Stevens, Emily; Walker, Robert; Nye, Edwin R.; Body, Dianne; Barclay, Leanne; Williams, Michael J. A.
Abstract : Objective . To examine long-term changes in physical function and body composition in coronary artery disease (CAD) patients participating in ongoing community-based cardiac rehabilitation (CR). Design . Thirty-four individuals (69.7 ± 8.2 years; 79% men) participated in this longitudinal observational study. Baseline and follow-up assessments included incremental shuttle walk, short physical performance battery, handgrip strength, chair stands, body composition, last year physical activity, and CR attendance. Results . Participants attended 38.5 ± 30.3 % sessions during 1.6 ± 0.2 year followup. A significant increase in 30-second chair stands (17.0 ± 4.7 to 19.6 ± 6.4, P < 0.001 ), body weight (75.8 ± 11.1 to 77.2 ± 12.1  kg, P = 0.001 ), and body fat (27.0 ± 9.5 to 29.1 ± 9.6 %, P < 0.001 ) and a decline in handgrip strength (36.4 ± 9.4 to 33.0 ± 10.6 kg·f, P < 0.001 ) and muscle mass (40.8 ± 5.6 to 39.3 ± 5.8 %, P < 0.001 ) were observed during followup. There was no significant change in shuttle walk duration. CR attendance was not correlated to observed changes. Conclusions . Elderly CAD patients participating in a maintenance CR program improve lower-body muscle strength but experience a decline in handgrip strength and unfavourable changes in body composition, irrespective of CR attendance.